Baseline Volumetric T2 Relaxation Time Histogram Analysis: Can It Be Used to Predict the Response to Intravenous Methylprednisolone Therapy in Patients With Thyroid-Associated Ophthalmopathy? - Liu, Ping; Luo, Ban; Chen, Lang; Wang, Qiu-Xia; Yuan, Gang; Jiang, Gui-hua; Zhang, Jing (Frontiers in Endocrinology, 2021)
Objective: Prediction of therapy response to intravenous methylprednisolone pulses (ivMP) is crucial for thyroid-associated ophthalmopathy (TAO). Image histograms may offer sensitive imaging biomarkers for therapy effect prediction. This study aimed to investigate whether pretherapeutic, multiparametric T2 relaxation time(T2RT) histogram features of extraocular muscles (EOMs) can be used to predict therapy response. Materials and Methods: Forty-five active and moderate-severe TAO patients, who were treated with standard ivMP and underwent orbital MRI before therapy, were retrospectively included in this study. The patients were divided into responsive (n=24, 48 eyes) and unresponsive group(n=21, 42 eyes) according to clinical evaluation. Baseline clinical features of patients and histogram-derived T2RT parameters of the EOMs were analyzed and compared. Logistic regression model was conducted to determine independent predictors, and a histogram features nomogram was formulated for personalized prediction. Results: Responsive group displayed lower values for 5th , 10th percentiles (P<0.050, respectively), and higher values for 75th, 90th, and 95th percentiles , skewness, entropy, and inhomogeneity (P<0.050, respectively) than unresponsive group. Multivariate logistic regression analysis showed that 95th percentile >88.1 [odds ratio (OR) = 12.078; 95% confidence interval (CI) =3.98-36.655, p<0.001], skewness >0.31 (OR=3.935; 95%CI=2.28-6.788, p<0.001) and entropy >3.41 (OR=4.375; 95%CI=2.604-7.351, p<0.001) were independent predictors for favorable response. The nomogram integration of three independent predictors demonstrated optimal predictive efficiency, with a C-index of 0.792. Conclusions: Pre-treatment volumetric T2RT histogram features of EOMs could function to predict the response to ivMP in patients with TAO. The nomogram based on histogram features facilitates the selection of patients who will derive maximal benefit from ivMP.